Gabon Poverty Assessment - World Bank (World Bank, Washington, DC, 2020)
Gabon's abundant endowment of natural resources, its strategic location, political stability, high urbanization, and youthful population create a broad but challenging development space for poverty reduction and shared prosperity. Immediately after independence the benefits of the oil boom propelled the country to upper-middle-income status and brought major progress in living conditions. The thriving resource sector triggered large migration flows of rural population to urban centers, resulting in the highest urbanization rate recorded in Africa. This urbanization process was characterized by increasing concentration of population and economic activities in a few cities along the coast, while the rest of the country became increasingly sparsely populated. The institutional and infrastructural foundations to ensure inclusive development and broad-based improvement of living conditions were not adequately set up. As a result, early economic and social achievements became unsustainable and have begun to fade with the decline of commodity prices and depletion of resources. Since its peak in the mid-1970s, real GDP per capita has halved. Today, persistent spatial inequalities are holding back lagging areas, unemployment is among the highest in Africa, and a large share of employment is informal and of low productivity. Poverty remains pervasive in the country. The incidence of poverty is particularly high in rural areas, but there is a disproportionate concentration of the poor in the main urban centers. Weak governance, coupled with lack of sound budgetary planning, prevent effective allocation of resources to promote social development and spatial integration. This Poverty Assessment uses the available household survey data (EGEP 2005 and 2017), the Demographic Health Surveys (DHS 2000 and 2012) and population census (RGPL 2013) to examine the nature of Gabon's poverty and looks forward asking what would be needed to sustainably reduce it.